2021
DOI: 10.1111/adb.13005
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic brain‐stimulation reward: A new procedure to re‐evaluate the rewarding versus aversive effects of cannabinoids in dopamine transporter‐Cre mice

Abstract: Despite extensive research, the rewarding effects of cannabinoids are still debated. Here, we used a newly established animal procedure called optogenetic intracranial self‐stimulation (ICSS) (oICSS) to re‐examine the abuse potential of cannabinoids in mice. A specific adeno‐associated viral vector carrying a channelrhodopsin gene was microinjected into the ventral tegmental area (VTA) to express light‐sensitive channelrhodopsin in dopamine (DA) neurons of transgenic dopamine transporter (DAT)‐Cre mice. Optoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 69 publications
3
22
0
Order By: Relevance
“…Interestingly, a recent study demonstrated that most cannabinoids suppress the reinforcing effects of optogenetic VTA DA neuron self-stimulation in mice, suggesting that cannabinoid receptor activation, in general, attenuates VTA DA reward or could exert aversive effects. This study also shows that VTA GABA and glutamate neurons express CB1Rs while VTA DA neurons express CB2Rs (Humburg et al, 2021). Given that VTA GABA neurons also provide inhibitory GABAergic input to LHb, it is possible that ELS-induced decreases in MAGL expression and persistent increases in eCB 2AG-CB1R-mediated suppression of VTA GABAergic input to the LHb promotes ELS-associated LHb hyperactivity.…”
Section: Els Potentially Impairs Ecb Signaling In the Lhbsupporting
confidence: 50%
“…Interestingly, a recent study demonstrated that most cannabinoids suppress the reinforcing effects of optogenetic VTA DA neuron self-stimulation in mice, suggesting that cannabinoid receptor activation, in general, attenuates VTA DA reward or could exert aversive effects. This study also shows that VTA GABA and glutamate neurons express CB1Rs while VTA DA neurons express CB2Rs (Humburg et al, 2021). Given that VTA GABA neurons also provide inhibitory GABAergic input to LHb, it is possible that ELS-induced decreases in MAGL expression and persistent increases in eCB 2AG-CB1R-mediated suppression of VTA GABAergic input to the LHb promotes ELS-associated LHb hyperactivity.…”
Section: Els Potentially Impairs Ecb Signaling In the Lhbsupporting
confidence: 50%
“…However, this view is not supported by our findings that neither CB2-immunostaining nor CB2 mRNA was detected in microglia in either normal healthy subjects ( Zhang et al, 2014 , 2017 , 2019 ) or in mice after acute administration of lipopolysaccharide, an endotoxin that causes severe neuroinflammation and microglia activation ( Zhang et al, 2014 ) or chronic administration of cocaine ( Zhang et al, 2017 ; 2021a ). In contrast, we demonstrated clear CB2 receptor expression in multiple phenotypes of neurons, including VTA DA neurons ( Zhang et al, 2014 , 2017 , 2019 ; Humburg et al, 2021 ), red nucleus glutamate neurons ( Zhang et al, 2021b ), and striatal GABA neurons ( Zhang et al, 2021a ; see a comprehensive review by; Jordan and Xi, 2019 ). Furthermore, chronic cocaine administration significantly up-regulates CB2 receptor expression in VTA DA neurons and NAc D1 receptor-expressing medium-spiny neurons, not in microglia ( Zhang et al, 2014 ; 2021a ).…”
Section: Discussionmentioning
confidence: 65%
“…Altogether, findings suggest a reciprocal interaction within the endocannabinoid system for modulating the reinforcing and psychomotor effects of cocaine. As discussed previously, this may occur through specificity of neurons expressing CB1Rs and CB2Rs, as recently described in the VTA [28,91,92]. Also, both CBRs are expressed on microglia and modulate neuroinflammatory processes, which may contribute to the pathophysiology of cocaine addiction (reviewed in [93]).…”
Section: Opposite Role Of Cb1rs and Cb2rs In Cocaine Adaptationsmentioning
confidence: 80%